Paradigma Baru Pengelolaan Institusi Dakwah: Urgensi Ilmu Manajemen Mewujudkan Majelis Taklim Ideal - Minangsih, Kalsum (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
One of the organizations that was growing and developing in Indonesia was taklim. This happens not only because of the collective consciousness of Muslims about the importance of studying the science of religion in daily life, more than that, taklim had become a container that could foster familiarity among the congregation. Taklim as a center of Islamic learning (Islamic Learning Institution) were recognized had a very large role in the intellectual life of the people and the nation. Currently, the existence of taklim felt increasingly important and was expected to play a greater role to solve various problems faced by the community. Most taklim managed traditionally and used the approach and concept lillahi taala reward that sometimes ignore the quality of the material that was tailored to the needs of the congregation, delivery methods, and so forth. Taklim certainly not enough just be a "Jiping", "Shalawatan", or "Hafmul" (memorized mouth) without knowing the letters of hijaiyyah. Thus, the pattern of management should be amended by introducing a new management scheme based on good management, improvement in terms of human resources (Ustadzah, Ustad), curriculum or materials, methods, and media used. This was the importance of a functioning management taklim made a planning, organization, implementation, control, and evaluation. Hopefully, with a new management-based on professionality, taklim could develop into the power of civil society and play a greater role in building the Indonesian Muslim community and the ideal taklim.